The dialogical theology of Hans Küng: Clash between the Catholic Mission and Islamic Da’wah in Indonesia - W.F. Riyanto; P.T. Galle’ (Acta Theologica)
This article explains the clash between the Catholic mission and Islamic Da’wah in Indonesia, as viewed from the theological perspective of Hans Küng (1928-2021). Küng was neither an orientalist nor an Islamologist; he was a Catholic theologian who contributed to interreligious dialogue for world peace. The primary source of data in this study is Küng’s work. The study findings assert that Küng proposed a dialogical-theological concept that is established on three pillars, namely autocritique of religion, global ethic, and dialogue among civilisations. Küng’s “dialogue among civilisations” is an antithesis to “clash of civilisations” proposed by S.P. Huntington (1927-2008). The findings indicate relevance in the Indonesian context. The three pillars are in line with the concept of Rational Islam, universal values in Pancasila, and the presence of the Center of Religious Harmony of the Republic of Indonesia.